EFEKTIVITAS PEMBERIAN TABLET FE DAN TABLET FE KOMBINASI VITAMIN C TERHADAP KADAR HB IBU POSTPARTUM DI WILAYAH KERJA PUSKESMAS KLAMBIR V KEBUN KEC. HAMPARAN PERAK TAHUN 2018 - Marini, Tri; Amanda, Nurul Ditta (JURNAL HEALTH REPRODUCTIVE, 2019)
One of the causes of iron deficiency anemia is the lack of adequate food intake for Fe sources and iron absorption with Vitamin C combination. The aim is to determine the effectiveness of giving fe tablets and combination tablets of vitamin C to hb levels at post partum mother at the working area of Klambir V community health care of Hamparan Perak sub district 2018. Quasy experimental research method with Two Group design pre-test and post-test. The population is all postpartum mothers. Sample of 20 peoples using purposive sampling. The statistical test used was the independent sample t test. The results showed that the average initial Hb level in postpartum mothers before consuming Fe was 10.51 g / dl after 4 weeks with an increase in Hb levels of 0.60 g / dl. In the intervention group, the mean initial Hb level was 10.46 g / dl. The average increase in Hb levels was g / dl in 4 weeks. The results of statistical tests showed that there was effectiveness in the administration of a combination of Vitamin C tablets with Hb levels in postpartum mothers with a p value of 0.000 (p <0.05). There was a significant effectiveness with the administration of a combination of vitamin C and Fe tablets to Hb levels in postpartum mothers. It is better to administer Fe tablets accompanied by vitamin C to help increase Hb levels